지방선거가 지방재정 지출에 미치는 영향 분석: 지방재정분석 건전성과 효율성 지표를 중심으로 - 윤정우; Jungwoo Yoon; 권영주; Youngjoo Kwon (국정관리연구, 2012)
본 연구는 지방선거가 지방재정 지출의 건전성과 효율성에 어떠한 영향을 미치는가를 분석하는데 목적이 있다. 이를 위해 전국기초자치단체를 대상으로 2006년 지방선거의 투표율과 득표율, 경쟁도를 독립변수로, 2007년 지방재정의 건전성과 효율성을 종속변수로 선정하여 분석하였다. 분석결과는 지방선거의 투표율이 지방재정 지출의 건전성 분야 중 인건비 지표와 효율성 분야 중 민간이전경비에 긍정적인 영향을 미치는 것으로 나타났다. 그러나 지방선거 투표율은 효율성 분야의 행사축제경비에 부정적인 영향을 미치는 것으로 나타났다. 따라서 지방선거에서 주민의 참여를 높이기 위한 노력과 함께 부정적 영향을 미치는 재정변수에 관한 관리가 필요하다. This study intends to analyze the effect of local elections on soundness and efficiency of the local finance expenditures. For this purpose, the turnout of voters in a local election, and vote for local governmen`s head and the competition among candidates were selected for the independent variables. And, soundness and efficiency of the management of local finances were selected for the dependent variables. The results of the analysis through multiple regression analysis are as follows; first, when turnout of voters in a local election rose, the index of financial soundness was decreased(the rate of personnel expenditures). This results mean that turnout of voters in a local election have been a positive influence on financial soundness. Second, when turnout of voters in a local election rose, the rate of event.festival expenditures was increased. However, the transfer rate of expenditures to private sector was decreased. This each result means that turnout of voters in a local election have been negative(event.festival expenditures) and positive(the transfer rate of expenditures to private sector) influence on financial efficiency. Consequently, the local finance variable negatively affected by participating rate of a local resident has to be managed with the effort for raising the local election participating rate of residents.